Regulation of osteoclast differentiation by β-glucan mediated by dectin-1 recognition and pharmacological application - ARIYOSHI, WATARU (ORAL THERAPEUTICS AND PHARMACOLOGY, 2022)
Coordinated co-stimulatory signals mediated by several immunoreceptors are important for the regulation of osteoclast differentiation. Dectin-1 is one of the pattern recognition receptors of β-glucan and is expressed on the surface of hematopoietic osteoclast precursor cells. In this review, we discuss the biological effects of β-glucans on bone-resorbing osteoclasts. Several β-glucans negatively regulate osteoclast differentiation by binding to dectin-1. Furthermore, we demonstrated the possibility of β-glucan as a candidate of osteoclast-targeting gene delivery system. Future studies concerning the relationship between the β-glucan structure and its biological effects on osteoclast are required for the development of novel pharmacological treatment for bone-related diseases.